Hughmillerites vancouverensis sp. nov. and the Cretaceous diversification of Cupressaceae1. Issue 12 (1st December 2014) - Atkinson, Brian A.; Rothwell, Gar W.; Stockey, Ruth A.
Abstract : Premise of the study: Two ovulate conifer cones, one of which is attached terminally to a short leafy shoot, reveal the presence of a new species of Hughmillerites in the Early Cretaceous Apple Bay flora of Vancouver Island, British Columbia, Canada. This ancient conifer expands the diversity of Cupressaceae in the Mesozoic and reveals details about the evolution of Subfamily: Cunninghamioideae. Methods: Specimens were studied from anatomical sections prepared using the cellulose acetate peel technique. Key results: Vegetative shoots have helically arranged leaves that are Cunninghamia ‐like. Seed cones have many helically arranged bract/scale complexes in which the bract is larger than the ovuliferous scale. Each ovuliferous scale has three free tips that separate from the bract immediately distal to an inverted seed. Several ovuliferous scales show interseminal ridges between seeds. Conclusions: This study documents a new extinct species of cunninghamioid conifers, Hughmillerites vancouverensis, expanding the record of the genus from the Late Jurassic to the Early Cretaceous. This new extinct species emphasizes the important role that conifers from subfamily Cunninghamioideae played in the initial evolutionary radiation of Cupressaceae. In light of recent findings in conifer regulatory genetics, we use H. vancouverensis to hypothesize that variations of expression in certain gene homologues played an important role in the evolution of the cupressaceous ovuliferous scale.